INDIKASI PELANGGARAN HAK CIPTA TERHADAP LAGU REMIX PADA APLIKASI TIKTOK - Nabila Khairunnisa (2023)
The ease of listening to music makes the types of music more diverse, with this convenience it also increases the level of creativity of the community in working in the music sector such as composing songs, this has resulted in rampant cases of copyright infringement of a song, especially on social media such as the TikTok application. Through this article, it is hoped that the public will know the signs and forms of violations that occur in the production and use of remix songs on the TikTok application and know the legal protection arrangements that copyright holders get if the song is remixed on the TikTok application. This research method uses a normative juridical method with a statutory regulation approach and uses primary legal material in the form of the Copyright Law and related regulations. The results of this study are indications of copyright infringement on remix songs that can be seen on the TikTok application, namely, the remix song itself is an arranged song or can be said to be a form of derivative art where the work is based on (at least) one work other. The act of remixing a song is a copyright infringement if you don't have permission, because in a creation that is protected there are also rights that must be protected, namely moral and economic rights. The responsibility for violating a remix song is fully held by the actor who remixes the song or the actor who uses the remix song without permission. Accountability can be carried out both civilly and criminally.